Genomic characterization of Staphylococcus aureus from Canastra Minas Artisanal Cheeses - Pineda, Ana P.Arellano (2023)
Canastra Minas Artisanal Cheese is produced in the Brazilian State of Minas Gerais using raw milk, rennet, and pingo, a natural endogenous starter culture (fermented whey) collected from the previous day’s production. Due to the use of raw milk, the product can carry microorganisms that may cause foodborne diseases (FBD), including Staphylococcus aureus. Genomic characterization of S. aureus is an important tool to assess diversity, virulence, antimicrobial resistance, and the potential for causing food poisoning due to enterotoxin production. This study is aimed at exploring the genomic features of S. aureus strains isolated from Canastra Minas Artisanal Cheeses. Multilocus sequence typing (MLST) classified these strains as ST1, ST5, and a new profile ST7849 (assigned to the clonal complex CC97). These strains belonged to four spa types: t008, t127, t359, and t992. We identified antimicrobial resistance genes with phenotypic correlation against methicillin (MRSA) and tetracycline. Virulome analysis revealed genes associated with iron uptake, immune evasion, and potential capacity for adherence and biofilm formation. The toxigenic potential included cyto- and exotoxins genes, and all strains presented the genes that encode for Panton-Valentine toxin and hemolysin, and two strains encoded 4 and 8 Staphylococcal enterotoxin (SE) genes. The results revealed the pathogenic potential of the evaluated S. aureus strains circulating in the Canastra region, representing a potential risk to public health. This study also provides useful information to monitor and guide the application of control measures to the artisanal dairy food production chain.